Aspergillus spp. and Bacillus spp. as Growth Promoters in Cotton Plants Under Greenhouse Conditions - Escobar Diaz, Paola Andrea; Gil, Oniel Jeremias Aguirre; Barbosa, Carlos Henrique; Desoignies, Nicolas; Rigobelo, Everlon Cid (Frontiers in Sustainable Food Systems, 2021)
This study aimed to verify the potential of three Aspergillus and Bacillus species as growth promoters in cotton plants under greenhouse conditions. The experiment was conducted with a completely randomized design with seven treatments (six microorganisms plus one control) and five replicates until the flowering stage at 70 days after emergence. The inoculation of cotton plants with Bacillus velezensis (Bv188) and Bacillus subtilis (Bs248 and Bs290) had a positive effect on total nitrogen extraction (899.31, 962.18, and 755.41 mg N/kg dry matter, respectively) compared to the control (459.31 mg N/kg dry weight), total phosphorus extraction (121.94, 124.31, and 99.27 mg P/kg dry matter, respectively) compared to the control (65.10 mg P/kg dry matter), and total dry matter (41.08, 43.59, and 49.86 g/plant, respectively) compared to the control (26.70 g/plant), as well as biomass carbon (72.26, 35.18, and 14.7 mg/kg soil, respectively). Cotton plants inoculated with Aspergillus brasiliensis (F111), Aspergillus sydowii (F112), and Aspergillus sp. (versicolor section) (F113) had higher total nitrogen extraction (953.33, 812.59, and 891.62 mg N/kg dry matter, respectively) compared to the control (459.31 mg N/kg dry matter), a higher total phosphorus (122.30, 104.86, and 118.45 mg P/kg dry matter, respectively) compared to the control (65.10 mg P/kg dry matter), a higher total dry matter (37.52, 37.41, and 53.02 g/plant) compared to the control (26.70 g/plant), and greater respiratory activity (14.98, 10.43, and 7.11 mg CO2/100 g soil, respectively) compared to the control (3.5 mg CO2/100 g soil). The fungi A. brasiliensis (F111) and A. sydowii (F112) promoted higher phosphorus absorption by cotton plants, which was reflected by the lower amount of nutrients in the soil (7.10 and 16.96 g P/dm3 soil) than in the control (26.91 g P/dm3 soil). The results suggest that B. subtilis 248 promoted an increase in phosphorus extracted from the roots and total and phosphorous compounds from the root dry matter and increased the value of soil respiratory activity, and this bacterium could be used as an inoculant in cotton crops.